Elephants and woodlands - comment by R. du Toit (Co-Editor) - du, Toit, (Pachyderm, 1986)
"Reviews work in elephant and diet, particularly the need for browse, in East Africa by Sikes (1968), McCullagh (1973), and White and Brown (1978), and by Cmelik and Ley (1977) in Zimbabwe. Quotes Lindsay’s query (Can we really say all elephants NEED a diet with a substantial browse fraction ..."" before mentioning that Richard Bell suggests more knowledge on physiological aspects (of elephants vis a vis diet) would be useful in the debate on elephants and woodlands. See Bell’s papers (1973, 1984, 1985)"